MAKAM, PESANTREN DAN TOKO KELONTONG - Ali Romdhoni (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2015)
For some Indonesian Muslim pilgrimage, not just merely spiritual issues or simply pray for deceased were given favors the grave, but has a significant correlation to the communities surrounding the tomb, especially the economy. On this basis, this paper seeks relationship photographing meals, boarding schools and grocery seller in Kajen, Pati. By using a qualitative approach through field studies by interviewing a variety of primary sources found that the tomb KH Mutamakkin in Kajen membrikan positive impact on the school and grocery merchants. Pesantren, madrasah in this case also, more vivid and dynamic development of the Islamic sciences, and massive. Temporal kelonotng for merchants, this opens up business opportunities, because of the many pilgrims who come every day to the tomb and the students or students living in lodgings in the boarding schools around the tomb.